›Wort für Wort‹ - Lektüren zum Werk von Oswald Egger - Endres, Martin / Simon (Theorie der Prosa, 2021)
Oswald Egger's extensive oeuvre has received only little reception in the field of literary studies. This might be due to the fact that, on account of their complex movements of language, these texts pose the question of whether and how they can be interpreted at all. This volume faces up to this interpretative task with close readings - word for word, paying special attention to the relationship between poetry and prose.